Calvinism and scholasticism in Vermigli's Doctrine of man and grace - Donnelly, John Patrick (Leiden, Netherlands Brill, 1976)
Includes bibliographical references and index.
Keywords: Vermigli, Peter Martyr, -- 1499-1562 -- Italian reformer; Man (Christian theology) -- historical of doctrines; Grace (theology) -- history of doctrines